Removal of Ochratoxin A in Saccharomyces cerevisiae Liquid Cultures - Bizaj, E.; Mavri, J.; ÄŒuÅ¡, F.; Raspor, A. (South African Journal of Enology and Viticulture, 2016)
The capacity for removal of ochratoxin A (OTA) during alcoholic fermentation was evaluated in batch systems with one commercial strain and one wild strain of Saccharomyces cerevisiae. Batch alcoholic fermentations were carried out in yeast extract-malt extract broth (YM) medium, with 18.0% glucose and OTA added to final concentrations of 3.48 and 4.95 ng/mL respectively. The removal capacity of each yeast strain was examined after completion of fermentation in batch culture and after extended contact with yeast biomass. The removal capacity of the yeast strains was also examined in stationary phase cultures. Stationary phase yeasts were studied with biomass harvested from the stationary phase of anaerobic fermentation, by incubation in phosphate buffer, with the addition of 5.00 ng/ mL of OTA. Removal studies with stationary phase cells were performed with viable and non-viable cells inactivated with Na-azide. The study showed that in growing phase cultures, OTA removal was significant only after extended contact with yeast biomass; up to 29.7% and 25.4% for wild yeast ZIM 1927 and commercial yeast Lalvin EC-1118 respectively, but not during alcoholic fermentation. In stationary phase cultures, viable and non-viable cells were not significantly different in OTA removal from the medium. This demonstrated that OTA was not metabolised, but possibly adsorbed by the yeast cells. The presence of OTA in synthetic media influenced yeast metabolism, causing the production of higher volatile acidity by 0.08 and 0.13 g/L for Lalvin EC-1118 and ZIM 1927 respectively, and lower concentrations of reducing sugar, by 0.32 g/L, but only for ZIM 1927.